The relationship between organisational culture and strategy formulation in South African firms - F. W. Struwig; E. E. Smith (South African Journal of Business Management, 2002)
In this article the relationship between organisational culture and strategy formulation in South African firms is investigated. The intention is to analyse whether South African firms with specific organisational culture types formulate strategies in the same manner. Literature available on the individual concepts of organisational culture and strategy formulation is extensive, but the relationship between the two concepts is generally ignored. During the empirical survey a self-administered questionnaire was send to 3000 firms. The culture type exhibited by firms was compared to the manner in which these firms formulate strategies. The findings confirm statistical significant relationships between firms with different organisational culture types and how strategies are formulated. Firms should therefore increase their emphasis on aligning culture and strategy.
Keywords: 650